2012
DOI: 10.1002/jbmr.1681
|View full text |Cite
|
Sign up to set email alerts
|

Sclerostin and DKK1 in postmenopausal osteoporosis treated with denosumab

Abstract: The bone mass benefits of antiresorbers in postmenopausal osteoporosis are limited by the rapid coupling of decreasing bone resorption with bone formation. Wnt signaling is involved in this coupling process during treatment with bisphosphonates, whereas its role during treatment with the anti-receptor activator of NF-κB ligand (RANKL) antibody denosumab is unknown. The study population includes patients participating in a placebo-controlled trial lasting 36 months: 19 women were on placebo and 24 on subcutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
52
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 31 publications
5
52
2
Order By: Relevance
“…1C). In contrast to our finding, Gatti et al found a significant increase in sclerostin levels in postmenopausal women treated with denosumab for osteoporosis compared with the placebo group [28]. The reasons for this discrepancy need to be elucidated.…”
Section: Discussioncontrasting
confidence: 53%
“…1C). In contrast to our finding, Gatti et al found a significant increase in sclerostin levels in postmenopausal women treated with denosumab for osteoporosis compared with the placebo group [28]. The reasons for this discrepancy need to be elucidated.…”
Section: Discussioncontrasting
confidence: 53%
“…This effect of bisphosphonates on WNTantagonist appears to be different from that we found in patients treated with denosumab (95), an antiresorptive drug that, suppressing RANKL activity, lowers the number not only of actively resorbing osteoclasts (as bisphosphonates do) but also of osteoclast precursors. In our study denosumab therapy was found to be associated with increasing SCL levels (as bisphosphonates treatment) but it was also associated with declining serum levels of DKK1 (95) and this might explain the apparent persistent slight positive unbalance between suppressed bone resorption and formation during denosumab treatment (96). The WNT-pathway is also involved in the response to bone anabolic agents.…”
Section: Sclerostincontrasting
confidence: 99%
“…Denosumab, a monoclonal RANKL antibody, not only effectively inhibits RANKL, which can lead to significant reduction of osteoclasts, but also increases osteoblastogenesis via inhibition of DKK1, which is antagonist of WNT/b-catenin pathway [4]. Therefore, these important mechanisms should be borne in mind as the major mechanisms for Denosumab for treatment of bone cyst.…”
mentioning
confidence: 99%